Responsible responsive design - Jehl, Scott (Book Apart (Series), 2014)
Responsive design has immeasurably improved multi-device, multi-browser visual layout but its only the first step in building responsively. Learn how to turn a critical eye on your designs as you develop for new contexts and screen features, speedy and lagging networks, and truly global audiences. --